Concepts, ontologies, and knowledge representation - Jakus, Grega; Milutinović, Veljko; Omerović, Sanida; Tomažič, Sašo (Springer briefs in computer science, 2013)
Recording knowledge in a common framework that would make it possible to seamlessly share global knowledge remains an important challenge for researchers. This brief is intended for those who want to get to know the field of knowledge representation quickly, or would like to be up to date with current developments in the field